2019
DOI: 10.1002/mus.26500
|View full text |Cite
|
Sign up to set email alerts
|

Balance impairment in pediatric charcot–marie–tooth disease

Abstract: Introduction: Balance impairment contributes to gait dysfunction, falls, and reduced quality of life in adults with Charcot–Marie–Tooth disease (CMT) but has been minimally examined in pediatric CMT. Methods: The CMT Pediatric Scale (CMTPedS) was administered to 520 children with CMT. Associations between balance function (Bruininks–Oseretsky Test of Motor Proficiency [BOT‐2]) and sensorimotor and gait impairments were investigated. Results: Daily trips/falls were reported by 42.3% of participants. Balance (BO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
1
22
0
3
Order By: Relevance
“…The vestibular system is most challenged when children encounter uneven, compliant, elevated, or inclined surfaces. In this study, Estilow et al reported differences between children with CMT and their healthy peers that continued to increase with age when vision was occluded. However, in conditions when the vestibular system was most challenged (standing on a balance beam), there were few between group differences at any age.…”
Section: Acknowledgmentmentioning
confidence: 50%
See 1 more Smart Citation
“…The vestibular system is most challenged when children encounter uneven, compliant, elevated, or inclined surfaces. In this study, Estilow et al reported differences between children with CMT and their healthy peers that continued to increase with age when vision was occluded. However, in conditions when the vestibular system was most challenged (standing on a balance beam), there were few between group differences at any age.…”
Section: Acknowledgmentmentioning
confidence: 50%
“…The adult experience is not directly applicable to children as the influence of development must be understood. In this report, Estilow et al examine the factors that contribute to balance impairment in children with CMT. Understanding the deficits underlying functional impairment would identify relevant outcome measures and identify therapeutic targets.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…Nossa análise da distribuição das diferentes posturas dos pés indicou predomínio de pés supinados (47,5%), seguido por pés normais (35%) e pronados (17%). A alta prevalência de pés supinados e as diferentes posturas dos pés encontradas na amostra são consistentes com estudos prévios (BURNS, RYAN, OUVRIER, 2009;BAPTISTA, et al, 2019;ESTILOW, et al, 2019). O desenvolvimento do pé cavo também parece guardar uma relação importante com a flexibilidade reduzida de tornozelo (AMINIAN, SANGEOZAN, 2008;BURNS, et al 2009;CORNETT, et al, 2017).…”
Section: Discussionunclassified
“…O pé cavo é caracterizado por retropé varo, arco longitudinal medial alto, flexão plantar de mediopé e antepé aduzido (Figura 1) (SCHEFFERS et al, 2012;KRAHENBUHL;WEINBERG, 2019) e, segundo Aminian e Sangeorzan (2008), está deformidade é inicialmente flexível, tornando-se rígida com a progressão do desequilíbrio muscular. Em adultos com CMT, a deformidade em cavo relaciona-se à perda da capacidade de deambulação (PADUA et al, 2008) e em crianças e adolescentes está associada a instabilidade de tornozelo e perda de equilíbrio (ROSE et al, 2015;ESTILOW et al, 2019) Figura 1-Deformidade de pé cavo em um participante com CMT de 11 anos de idade (Classificação do Índice Postural do Pé de -10 para os pés direito e esquerdo) Fonte: Arquivo Próprio O déficit somatossensorial é causado pela modificação de fibras sensoriais de calibre grosso, médio e fino (NARDONE, et al, 2000;VAN DER LINDEN et al, 2010;LENCIONI et al, 2015). As fibras sensoriais de calibre grosso e médio atuam principalmente na sensação de movimento e posição das articulações e sensação de vibração.…”
Section: Doença De Charcot-marie-tooth: Uma Visão Geralunclassified
See 1 more Smart Citation